2016
DOI: 10.1080/09540121.2016.1199846
|View full text |Cite
|
Sign up to set email alerts
|

Organization of care for persons with HIV-infection: a systematic review

Abstract: The objective of this systematic review was to examine the effectiveness of the organization of care: case management, multidisciplinary care, multi-faceted treatment, hours of service, outreach programs and health information systems on medical, immunological, virological, psychosocial and economic outcomes for persons living with HIV/AIDS. We searched PubMed (MEDLINE) and 10 other electronic databases from 1 January 1980 to April, 2012 for both experimental and controlled observational studies. Thirty-three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Multidisciplinary providers who work in team-based care models have been shown to improve clinical outcomes among HIV patients [70][71][72][73] . This study provided examples of collaborations in which practitioners worked together to meet the diverse needs of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Multidisciplinary providers who work in team-based care models have been shown to improve clinical outcomes among HIV patients [70][71][72][73] . This study provided examples of collaborations in which practitioners worked together to meet the diverse needs of patients.…”
Section: Discussionmentioning
confidence: 99%
“…One ecological study showed that in low income areas, car ownership was associated with a higher proportion of individuals linked to care, and high access to public transportation was associated with a higher proportion of patients with suppressed HIV viral load (Goswami et al, 2016). When people live in areas of lower population density and HIV services are far away, the solutions to transportation barriers are not easy; mobile health clinics (Garrett, 1995; Kahn, Moseley, Thilges, Johnson, & Farley, 2003) and case management (Handford, Tynan, Agha, Rzeznikiewiz, & Glazier, 2016) can be effective methods of increasing retention in care and improving HIV outcomes.…”
Section: Discussionmentioning
confidence: 99%